Evaluation of preoperative and intraoperative red blood cell transfusion practices at Maputo Central Hospital, Mozambique. Issue 1 (21st May 2013) - Burke, Zachary D.C.; Chen, James B.; Conceicao, Celson; Hoffman, Risa M.; Miller, Lee T.; Taela, Atanasio; DeUgarte, Daniel A.
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to evaluate preoperative and intraoperative blood transfusion practices in Hospital Central (Maputo, Mozambique) and estimate the number of potentially avoidable transfusions. Study Design and Methods A retrospective cohort study was performed. Age, comorbidities, hemoglobin (Hb), the potential for blood loss, and units of red blood cell (RBC) transfusions were recorded. Preoperative transfusions were evaluated to determine whether they met criteria established by the Mozambican Ministry of Health as well as proposed guidelines based on more restrictive protocols. Avoidable blood transfusions were defined as those preoperative transfusions that were not indicated based on these guidelines. Multivariate logistic regression was used to identify factors that predicted transfusion. Results A total of 205 patients (age range, 0.1‐86 years) underwent surgery in the main operating room during the 2‐week study period. Overall, 35 (17%) patients received 68 transfusions. Of these, 36 transfusions were given preoperatively and 32 were given intraoperatively. Thirty‐six percent of preoperative transfusions were avoidable according to national guidelines. Ninety‐two percent were avoidable using more restrictive guidelines. The primary predictors of preoperative blood transfusion were lower Hb (odds ratio [OR], 0.390/1 g/dL; p < 0.0001) and the potential for blood loss (OR, 3.73; p = 0.0410). Conclusions Adherence to existing Hb thresholds recommended by national blood transfusion guidelines could significantly reduce the number of transfusions and the association risk of transfusion‐transmissible infections. Adoption of more restrictive guidelines is recommended to further improve blood transfusion utilization and further reduce the transmission risk of human immunodeficiency virus and hepatitis.